(untitled) (Journal of the College of Basic Education, 2023)
The research included five chapters:Chapter One: Introducing the researchThe introduction dealt with the importance of sports activities in general, and gymnastics in particular. The research included knowing some of the biokinematic variables of the skill (handstand followed by frontal rolling) by analyzing the skill, diagnosing the most important errors in its motor path, and finding out the weaknesses when performing it to prepare a proposed training curriculum that includes exercises to withstand the constant force, based on correct scientific foundations to avoid such points. These exercises are a corrective and developmental approach that helps in addressing weaknesses in the technical performance of the selected research skill. As for the problem of the research, there is weakness in the technical performance of the skill (handstand followed by forward rolling), which leads to the students obtaining low degrees. To a large deduction from the grades of performance, which then affects the final grade of the students.